If it's not what You are looking for type in the equation solver your own equation and let us solve it.
122x-122=16(7x-7)
We move all terms to the left:
122x-122-(16(7x-7))=0
We calculate terms in parentheses: -(16(7x-7)), so:We get rid of parentheses
16(7x-7)
We multiply parentheses
112x-112
Back to the equation:
-(112x-112)
122x-112x+112-122=0
We add all the numbers together, and all the variables
10x-10=0
We move all terms containing x to the left, all other terms to the right
10x=10
x=10/10
x=1
| -6n+20-8n+7=n-43 | | X^4+(x+7)+x=127 | | $21+0.07x=0.12x | | 3x(+34)=× | | (6x+5)(7x-4)=79 | | 3x+34=x | | 10x•3=8x | | (10+x)•3=8x | | 4(3x+1)=17x+3-5x+1 | | -6n+15-14n+7=n-76 | | 11x+4=-11x+-11 | | (10+x)×3=8x | | 2.4+10m=7.71 | | -6n+15-14n+7=n-75 | | 4x+16x-7=5(4x+6) | | 4k=60+20 | | 2y-67=24 | | 3(x+3)+3(x+6)=45 | | 16)^(2x-1)=128 | | 4x²=29x+63 | | 4u-3u+4=15 | | 27-4(x-2)=11 | | 5x+1/2x=22 | | 3(z+1)+4(z+0.3)=20z+0.95 | | 0.25x-3=-5 | | 8/5x=90 | | (z+6)^2=-36 | | -3-0.25x+3x=30 | | 5(u-1)-1=-5(-6u+2)-9u | | 9u+36=7(u+4) | | -4n+15-5n+7=n-43 | | -16=-6w+2(w+6) |